2017
DOI: 10.1187/cbe.16-01-0029
|View full text |Cite
|
Sign up to set email alerts
|

A Program Aimed toward Inclusive Excellence for Underrepresented Undergraduate Women in the Sciences

Abstract: This paper describes an evaluation of Smith College’s Achieving Excellence in Mathematics, Engineering, and Science Scholar program, developed to improve outcomes for underrepresented women in science. AEMES Scholars’ academic record data reveal benefits over time and relative to peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Ghee et al (2018) focuses on professional development activities for students at minority-serving institutions, closely tracking the success of these students through career pathway measures. Finally, a comparison study by Katz et al. (2017) convincingly demonstrates STEM persistence for female students of color in particular.…”
Section: Discussion Implications and Directions For Future Researchmentioning
confidence: 82%
“…Ghee et al (2018) focuses on professional development activities for students at minority-serving institutions, closely tracking the success of these students through career pathway measures. Finally, a comparison study by Katz et al. (2017) convincingly demonstrates STEM persistence for female students of color in particular.…”
Section: Discussion Implications and Directions For Future Researchmentioning
confidence: 82%
“…For instance, mentoring for gender equality tends to focus on the basic idea of a woman, not the multiple expressions of womanhood (Thomas et al, 2015). The Katz et al (2017) examination of Smith College's Achieving Excellence in Mathematics, Engineering, and Science (AEMES) scholars program highlights the outcomes for undergraduate WOC. Notably, in a study on creating inclusive learning environments to excel, the criteria for WOC implied traditional gender norms.…”
Section: Catch-all Approachmentioning
confidence: 99%
“…This supports research conducted by Shin, Levy, and London (2016) where women reported an increase in perceived fit in STEM after reading biographies of successful STEM role models who were also women and findings from Herrmann et al (2016) where women were more likely to persist in STEM courses after reading letters of encouragement from women role models. Aside from traditional one-onone mentoring programs (Carpi et al 2017), there are also successful mentoring groups specifically for minority groups (Katz et al 2017;Snead-McDaniel 2010), and communal mentors (Fuesting and Diekman 2017).…”
Section: Learning Communitiesmentioning
confidence: 99%